2000
DOI: 10.1001/archsurg.135.11.1256
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of 3-Dimensional Reconstructions on Operation Planning in Liver Surgery

Abstract: Background: Operation planning in liver surgery depends on the precise understanding of the 3-dimensional (D) relation of the tumor to the intrahepatic vascular trees. To our knowledge, the impact of anatomical 3-D reconstructions on precision in operation planning has not yet been studied. Hypothesis: Three-dimensional reconstruction leads to an improvement of the ability to localize the tumor and an increased precision in operation planning in liver surgery. Design: We developed a new interactive computerbas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
107
0
19

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(127 citation statements)
references
References 16 publications
1
107
0
19
Order By: Relevance
“…Currently, some computer simulators are available for surgical training, but most have limited, pre-programmed scenarios [1,4,6]. In liver surgery, the use of an image processing workstation allows one to calculate resection volume and visualize completion images [16,17]. However, this existing system is not interactive, so the steps of the operation cannot be simulated.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, some computer simulators are available for surgical training, but most have limited, pre-programmed scenarios [1,4,6]. In liver surgery, the use of an image processing workstation allows one to calculate resection volume and visualize completion images [16,17]. However, this existing system is not interactive, so the steps of the operation cannot be simulated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in the field of liver surgery planning evaluated only the impact of 3D visualization [5] and virtual resection planning [6]. Thereby, the planning data was always compared with a presentation of 2D CT images.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the three-dimensional presentation did indeed lead to improved OP representation. Overall, three-dimensional presentation led to approaching a 31% higher precision in tumor localization and improvement in resection recommendations [20,21] . This study also illustrated the disadvantage of this method.…”
Section: A B Cmentioning
confidence: 99%